(untitled) (American Journal of Development Studies, 2025)
Self-realization, the process of understanding oneself, has been a popular subject in philosophy, psychology, and spiritual traditions. “The Alchemist” by Paulo Coelho (1998), is the literary embodiment of this very idea as the book follows the personal odyssey of its hero and his pursuit of self-realisation and happiness. This paper explores how the novel embodies the philosophy of self or self-realization, going back and forth between Western philosophy (Socrates, Nietzsche, Sartre), Eastern thought (Vedanta, Buddhism), psychology (Carl Jung’s individuation process, Maslow’s self-actualization), and Sufi mysticism. This paper offers a qualitative textual analysis of how these philosophical frameworks and psychological constructs coincide with the novel’s themes, symbols and characterisation. Results demonstrate that Santiago’s journey embodies the existential (existentialist, mystical and psychological) ideas about self-awareness, personal transformation, and destiny. The analysis also reveals how Coelho’s work promotes intuition, persistence and spiritual awakening as fundamental values needed to attain one’s “Personal Legend.” This analysis situates these ideas within broader philosophical traditions, demonstrating how literature can be a means of deep existential reflection. This work offers value to those interested in literature, philosophy, and psychology by illustrating how “The Alchemist” reflects general human dilemmas in the process of self-actualization. The research confirms that we continue to learn who we are from our interactions with the world around us and the guided journey of reflection, resulting in a life of integration and purpose.